2007
DOI: 10.1111/j.1600-0447.2006.00976.x
|View full text |Cite
|
Sign up to set email alerts
|

Mental distress and quality of life in the hard of hearing

Abstract: General psychiatrists need to be aware that patients who are hard of hearing may be even more isolated than deaf people in a signing community. Hard of hearing patients with unsatisfactory hearing aids can be greatly assisted by cochlear implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(61 citation statements)
references
References 9 publications
6
47
0
7
Order By: Relevance
“…Examples include: Present State Examination (Baker et al, 2003), the Brief Symptom Inventory (Brosig et al, 2007;Cuculi et al, 2006;Fellinger et al, 2007;Mansbach et al, 2005), and the BussDurkee Hostility Inventory (Bag et al, 2005). All were primarily designed to identify specific pathologic disorders, and validated using dysfunctional clinical populations with abnormal statistical distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include: Present State Examination (Baker et al, 2003), the Brief Symptom Inventory (Brosig et al, 2007;Cuculi et al, 2006;Fellinger et al, 2007;Mansbach et al, 2005), and the BussDurkee Hostility Inventory (Bag et al, 2005). All were primarily designed to identify specific pathologic disorders, and validated using dysfunctional clinical populations with abnormal statistical distributions.…”
Section: Introductionmentioning
confidence: 99%
“…Em relação aos aspectos abordados sobre a comunicação entre familiares e as crianças, sabe-se que a interferência na comunicação das pessoas com deficiência auditiva é uma condição permanente, que acarreta graves consequências no seu desenvolvimento social, emocional e cognitivo 21 . Desta forma, ao analisarmos as respostas para esse questionário, verifica-se que na questão 1 a maioria (65%) assinalou que às vezes há dificuldades de comunicação quando estão em locais diferentes da casa, em contrapartida, apenas 15% afirmaram que nunca ocorre tal dificuldade.…”
Section: Discussionunclassified
“…Cited problems include communication difficulties in group situations, understanding conversational nuances, and learned helplessness (Heydebrand et al, 2005;Hyde, Punch, & Komesaroff, 2010). Studies have also reported higher levels of mental distress, depression, interpersonal sensitivity, phobic anxiety, substance abuse, and hostility in deaf individuals compared with population norms (Brunnberg, Boström, & Berglund, 2007;de Graaf & Bijl, 2002;Fellinger et al, 2007;Jones, E.G., Ouellette, & Kang, 2006;Monzani et al, 2008). Irritability, feelings of inferiority, and phobias can create a mutually impacting cycle of social rejection and psychological dejection, and deliberate selfseclusion from social and professional activities (Heydebrand et al, 2005).…”
Section: Mental Health and Professional And Social Participation In mentioning
confidence: 99%